Analyzing Kindergarten Teachers’ Understanding and Practices in Integrating Warak Ngendog Culture into Classroom Learning in Semarang City - Ni'matul Latifah; Edi Waluyo (Universitas Sebelas Maret, 2026)
Learning in early childhood plays an important role in shaping children’s character and identity. Rapid technological development requires local culture-based learning to be prioritized in order to strengthen children's identity contextually and sustainably. Warak Ngendog, as a local cultural identity of Semarang City, contains values of tolerance, diversity, and unity that are important to introduce from an early age. However, it is not yet clearly known how far kindergarten teachers understand this culture and how it is applied in learning. This study aims to analyze kindergarten teachers’ understanding in integrating Warak Ngendog culture into the learning process in Semarang City. This research used a descriptive quantitative approach with data collected through questionnaires distributed to 136 kindergarten teachers selected using simple random sampling. The instrument was tested for validity and reliability. Data were analyzed using percentage techniques and categorized into levels of understanding. The results showed that the overall level of teacher understanding was in the good category (79%), with the highest scores in tolerance (85%) and knowledge (81%). Teachers have also applied cultural approaches in learning, such as introducing regional songs, traditional clothing, and folklore. The introduction of Warak Ngendog culture contributes to character building and strengthening children's identity from an early age.